The application of firefly algorithm in an adaptive emergency evacuation centre management (AEECM) for dynamic relocation of flood victims - Che Pa, Noraziah; Hashim, Nor Laily; Yusof, Yuhanis; Hussain, Azham (AIP Publishing LLC, 2016)
Flood evacuation centre is defined as a temporary location or area of people from disaster particularly flood as a rescue or precautionary measure. Gazetted evacuation centres are normally located at secure places which have small chances from being drowned by flood.However, due to extreme flood several evacuation centres in Kelantan were unexpectedly drowned.Currently, there is no study done on proposing a decision support aid to reallocate victims and resources of the evacuation centre when the situation getting worsens.Therefore, this study proposes a decision aid model to be utilized in realizing an adaptive emergency evacuation centre management system. This study undergoes two main phases; development of algorithm and models, and development of a web-based and mobile app.The proposed model operates using Firefly multi-objective optimization algorithm that creates an optimal schedule for the relocation of victims and resources for an evacuation centre.The proposed decision aid model and the adaptive system can be applied in supporting the National Security Council’s respond mechanisms for handling disaster management level II (State level) especially in providing better management of the flood evacuating centres.